Stridulatory file and calling song of two populations of the tropical bush cricket Eneoptera surinamensis (Orthoptera, Gryllidae, Eneopterinae) - Miyoshi, Akio R. [UNESP]; Zefa, Edison; Martins, Luciano de P.; Dias, Pedro G. B. S.; Drehmer, César J.; Dornelles, José E. F. (Fundação Zoobotânica do Rio Grande do Sul, 2007)
Este estudo caracteriza a ultramorfologia da nervura estridulatória e o som de chamado de duas populações de Eneoptera surinamensis (De Geer, 1773) de Foz do Iguaçu, Paraná e Rio Claro, São Paulo, distantes cerca de mil quilômetros. Os dentes que compõem a nervura estridulatória têm forma de concha, os maiores presentes na região mediana da fileira, reduzindo gradualmente de tamanho em direção às extremidades. Os espécimes de Foz do Iguaçu têm a nervura estridulatória com 1,89 mm ± 0,15 de comprimento, 82 ±9,8 dentes, sendo 43,76 ± 5,94 (n=15) por milímetro, enquanto os de Rio Claro 1,96 ± 0,19 mm de comprimento, 87 ± 9,81 dentes e 44,52 ± 4,61 dentes por mm (n=15). As diferenças observadas entre as populações não são estatisticamente significantes. O som de chamado é composto por um trill contínuo que alterna dois conjuntos de notas, com padrões temporais distintos.

This study characterizes the calling song and ultramorphology of the stridulatory file of two geographically isolated populations of the tropical bush cricket Eneoptera surinamensis (De Geer, 1773) from city of Foz do Iguaçu, state of Paraná, and town of Rio Claro, state of São Paulo, Brazil, distant 1,000 Km from each other. The teeth are shell-shaped, the larger ones are distributed in the medium region of the file, decreasing gradually in size towards the edges. Specimens from Foz do Iguaçu have a file with 82 ± 9.8 teeth, length=1.89 mm ± 0.15 with 43.76 ± 5.94 teeth per mm (n=15). Specimens from Rio Claro present a file with 87 ± 9.81, length=1.96 ± 0.19 mm with 44.52 ± 4.61 teeth per mm (n=15). Statistical differences found between the two populations are not significant. The calling song is an uninterrupted trill that alternates two sets of notes distinct for its temporal features.
Fileira estridulatória e som de chamado de duas populações do grilo tropical Eneoptera surinamensis (Orthoptera, Gryllidae, Eneopterinae)
Keywords: Grylloidea; bioacústica; sonograma; pars stridens; Grylloidea; bioacoustic; sonogram; pars stridens